THE ROLE OF INTERNET TECHNOLOGIES IN THE EDUCATION AND SPIRITUAL DEVELOPMENT OF YOUTH (Web of Teachers: Inderscience Research, 2024)
This article enlightens the analysis of the impact of Internet on the spiritual of youth from the point of social-philosophical view. Also, there studied the priorities of preservation of young people’s consciousness from harmful influences and ideas coming through the Internet. Nowadays when the information has strengthened, there were analyzed processes of fighting for being occupied of youth consciousness by different means and resources through internet. The role and importance of global internet is increasing now and as a result, there were identified positive and negative features of it.